(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Case presentation: A 45-year-old nulliparous patient presented with a long-standing history of genital discomfort in the form of friction, laceration, and dyspareunia. She was also esthetically displeased with her labia minora, which she considered too large and long. Her labia minora appearance was also noted to cause emotional distress. The patient requested labia minoraplasty. Despite correct technique selection, she was noted to have notching, fenestration, and pigment mismatch eight weeks postoperatively, and required revision surgery. Discussion: Wedge resection versus edge trimming is an active topic in cosmetic gynecology. Patient selection and hypertrophied labia minora are important considerations in technique selection. These have a bearing on the eventual esthetic appearance and development of untoward effects. Conclusion: Even with the correct technique selection for a specific type of labial hypertrophy, untoward effects may develop postoperatively, requiring reconstruction or revision later.